Cholate-modified polymer-lipid hybrid nanoparticles for oral delivery of quercetin to potentiate the antileukemic effect - Yin J (Dove Medical Press, 2019)
Juntao Yin,1 Yantao Hou,2 Xiaoyong Song,3 Peiqing Wang,1 Yang Li11Department of Pharmaceutics, Huaihe Hospital Affiliated to Henan University, Kaifeng, People’s Republic of China; 2Henan Vocational College of Applied Technology, Kaifeng, People’s Republic of China; 3School of Pharmacy, Henan University, Kaifeng, People’s Republic of ChinaBackground: Quercetin (QUE) shows a potential antileukemic activity, but possesses poor solubility and low bioavailability.Purpose: This article explored the bile salt transport pathway for oral deliver of QUE using cholate-modified polymer-lipid hybrid nanoparticles (cPLNs) aiming to enhance its antileukemic effect.Methods: QUE-loaded cPLNs (QUE-cPLNs) were developed through a nanoprecipitation technique and characterized by particle size, entrapment efficiency (EE), microscopic morphology and in vitro drug release. In vitro cellular uptake and cytotoxicity of QUE-cPLNs were examined on Caco-2 and P388 cells; in vivo pharmacokinetics and antileukemic effect were evaluated using Sprague Dawley rats and leukemic model mice, respectively.Results: The prepared QUE-cPLNs possessed a particle size of 110 nm around with an EE of 96.22%. QUE-cPLNs resulted in significantly enhanced bioavailability of QUE, up to 375.12% relative to the formulation of suspensions. In addition, QUE-cPLNs exhibited excellent cellular uptake and internalization capability compared to cholate-free QUE-PLNs. The in vitro cytotoxic and in vivo antileukemic effects of QUE-cPLNs were also signally superior to free QUE and QUE-PLNs.Conclusion: These findings indicate that cPLNs are a promising nanocarrier able to improve the oral bioavailability and therapeutic index of QUE.Keywords: quercetin, polymer-lipid hybrid nanoparticles, bile salt, bioavailability, leukemia